FAKE NEWS AND DISINFORMATION: ETHICAL IMPACTS AND RESPONSIBILITIES - Nurdiana Fariha ‘Ainuddin; Nur Aimi Atirah Abdul Malik; Muhammad Izmeer Adil Aruan; Salliza Md Radzi (Journal of Islamic, Social, Economics and Development, 2023)
Ethics considers how people interact with one another and with nature, as well as their own freedom, responsibility, and sense of justice. Therefore, this study aims to examine the ethical implications of fake news, disinformation campaigns, and misinformation spread on social media platforms. Furthermore, this study also investigates the impact on public discourse, democracy, and the ethical responsibilities of social media companies and users in combating disinformation. Many fake news is widely disseminated without ensuring such information from trusted sources. The literature review research methodology was employed to answer the objectives of the study. The information was explored from online databases by reviewing existing literature through academic journals. People were acting out of control without checking if the news is true or simply fake. Many people share fake news because they find it exciting and relevant to what is happening in the world. The journal article expands our understanding of how disinformation and fake news spread on the platform. The conclusion of this paper will be beneficial for readers and help them in detecting the negative effects by spreading it.